Investigation of bearing inner ring-cage thermal characteristics based on CdTe quantum dots fluorescence thermometry. (5th March 2017) - Yan, Ke; Yan, Bei; Li, Ben Q.; Hong, Jun
Highlights: A novel method for bearing inner ring/cage thermal monitoring was first presented. Temperature rise of bearing inner ring in real work condition was obtained. The rotation speed (6000 r/min) measured here is much higher than all the existing methods. Abstract: A novel wireless temperature sensor and non-intrusive temperature measurement method for bearing monitoring were proposed in this paper, based on spectrum parameter analysis of CdTe quantum dots films. The CdTe QDs were synthesized and were used in constructing of a sensor film by means of Layer-by-layer Electrostatic Self-assembly method. The fluorescence spectrum properties of the sensor were characterized. At rotation speed 5000–6000 r/min, bearing cage and inner ring temperature were presented first in this paper by the CdTe QDs sensor. The results were verified by theoretical analysis and by thermocouples, with an error typically below 10% or smaller. Compared to the traditional outer ring monitoring, the measurement and monitoring of bearing rolling elements is of very importance, especially at high rotation speed.